The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10646-012-0878-3
|View full text |Cite
|
Sign up to set email alerts
|

Using sets of behavioral biomarkers to assess short-term effects of pesticide: a study case with endosulfan on frog tadpoles

Abstract: Pesticides and other chemicals often have detrimental effects at environmental concentrations. Many amphibian species are particularly threatened because of their susceptibility but also because wetlands are often polluted. Behavioral assessments of toxicity have the advantage of showing sublethal effects but quantitative measures at varied scales of integrations are rarely considered together. In this study, we aimed at showing that these behavioral endpoints could be differently affected across time and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 63 publications
3
23
1
Order By: Relevance
“…This increase of serotonin enhances satiety and inhibits feeding. Our results on food acquisition are in agreement with previous studies on amphibian tadpoles which showed that feeding rates were decreased or even suppressed after endosulfan exposure (Broomhall and Shine, 2003;Denoël et al, 2012). This is also consistent with the high observed level of serotonin and suggests that the decrease of feeding activity may be linked to the increase of serotonin concentration in the brain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This increase of serotonin enhances satiety and inhibits feeding. Our results on food acquisition are in agreement with previous studies on amphibian tadpoles which showed that feeding rates were decreased or even suppressed after endosulfan exposure (Broomhall and Shine, 2003;Denoël et al, 2012). This is also consistent with the high observed level of serotonin and suggests that the decrease of feeding activity may be linked to the increase of serotonin concentration in the brain.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the fact that Sillar et al (1998) used high doses, at least 400-fold higher than the ones used in the present paper. Previous studies showed also that convulsions, which can result from uncorrected neural discharges, were not produced at low environmental endosulfan concentrations (Brunelli et al, 2009;Denoël et al, 2012). Finally, exposure to SSRI (Selective Serotonin Reuptake Inhibitor) causes a growth reduction of 35% in X. laevis (Conners et al, 2009) but no effects of endosulfan were found on growth rates in the present study whereas previous research highlighted the presence or absence of effects.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The use and application of biomarkers in ecotoxicology have extensively been discussed since their proposal as useful predictors of ecologically relevant effects (Shugart et al 1992; Forbes et al 2006). In recent years, the classical concept has been extended to include higher biological levels (Handy et al 2003; Denoël et al 2012). In herpetological ecotoxicology, lethal and sublethal endpoints like mortality and morphological and behavioral alterations during embryonic and larval development were the first and most amply described biomarkers of exposure (Venturino et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As a measure of developmental hazard, the teratogenic potential (TP) (Aronzon et al, 2011a) was estimated as the ratio between the NOEC value for lethality and sublethal effects and it was compared with the maximal value of 1.5 (ASTM, 1993) which implies large separation of the mortality and malformations concentration ranges and, therefore, a great potential for all embryos to be malformed in absence of significant embryo mortality. Behavioral alterations such as abnormal fast rotations which are a sign of neurotoxic stress; lying on the lateral or dorsal side, abnormal breathing, feeding and swimming patterns were evaluated (Denoël et al, 2012). Smooth movements of the Petri-dishes, followed by stimulation with a light source were done.…”
Section: Toxicity Experimental Protocolsmentioning
confidence: 99%